The Sharpe ratio : statistics and applications - Pav, Steven E. (Boca Raton : Taylor and Francis, 2022)
The Sharpe ratio is the most widely used metric for comparing theperformance of financial assets. The Markowitz portfolio is the portfolio withthe highest Sharpe ratio. The Sharpe Ratio: Statistics and Applications examines the statistical propertiesof the Sharpe ratio and Markowitz portfolio, both under the simplifyingassumption of Gaussian returns and asymptotically. Connections aredrawn between the financial measures and classical statistics includingStudent's t, Hotelling's T^2, and the Hotelling-Lawley trace. Therobustness of these statistics to heteroskedasticity, autocorrelation, fat tails, and skew of returns are considered. The construction of portfolios to maximizethe Sharpe is expanded from the usual static unconditional model to include subspace constraints, heding out assets, and the use of conditioning information on both expected returns and risk. {book title} is the most comprehensivetreatment of the statistical properties of the Sharpe ratio and Markowitzportfolio ever published. Features: * Material on single asset problems, market timing, unconditional and conditional portfolio problems, hedged portfolios.* Inference via both Frequentist and Bayesian paradigms.*A comprehensive treatment of overoptimism and overfitting of trading strategies.*Advice on backtesting strategies.*Dozens of examples and hundreds of exercises for self study. This book is an essential reference for the practicing quant strategist and the researcher alike, and an invaluable textbook for the student. Steven E. Pav holds a PhD in mathematics from Carnegie Mellon University, and degrees in mathematics and ceramic engineering sciencefrom Indiana University, Bloomington and Alfred University.He was formerly a quantitative strategist at Convexus Advisors and CerebellumCapital, and a quantitative analyst at Bank of America.He is the author of a dozen R packages, including those for analyzing the significance of the Sharpe ratio and Markowitz portfolio.He writes about the Sharpe ratio at https://protect-us.mimecast.com/s/BUveCPNMYvt0vnwX8Cj689u?domain=sharperat.io.
Mathematics
Steven E. Pav holds a PhD in mathematics from Carnegie Mellon University, and degrees in mathematics and ceramic engineering science from Indiana University, Bloomington and Alfred University. He was formerly a quantitative strategist at Convexus Advisors and Cerebellum Capital. He is the author of a dozen R packages, including those for analyzing the significance of the Sharpe ratio and Markowitz portfolio. He writes about the Sharpe ratio at http://www.sharperat.io.
English
Print version record.
Keywords: Risk-return relationships; Investment analysis; Rapport risque-rendement.; Analyse financière.; Investment analysis; Risk-return relationships